Dampak Covid-19 Terhadap Kinerja Saham Emiten Indeks LQ 45 - rahmawati, Meita; Patmawati, Patmawati; Dwirini, Dwirini (Catholic University Musi Charitas, 2022)
This research is an event study research, where the researcher wants to see the content of information after the announcement of the Covid 19 case. The researcher uses a quantitative descriptive method with non-parametric analysis, using the Wilcoxon test to see the effect of performance with abnormal returns and trading activity before and after the announcement of an event. incident. Researchers used an observation period of 3 days before the announcement and 3 days after the announcement of Covid 19 by the President of the Republic of Indonesia. Hypothesis testing shows that the Z value of -2,469 with Asymp Sig (2-tailed) of 0.014 is smaller than 0.05, proving that there is a difference in abnormal returns before the announcement and after the announcement of the event, but on the contrary, testing trading activities before and after the announcement. shows a Z value of -1.838 with Asymp Sig (2-tailed) of 0.066, higher than the value of 0.05, so it can be concluded that there is no difference in the increase or decrease in stock trading volume activity significantly before and after the announcement of Covid-19. Keyword: Abnormal Return; Trading Volume Activity; Index LQ 45; Coronavirus.